Alfalfa Weevil Management in Kansas: II. Non-chemical controls - Higgins, Randall A.; Blodgett, Sue L.; Lenssen, Andrew W. (My University, 1989)
This publication provides recommendations that emphasize integrated management strategies for controlling insect problems.
MF918_1989_04
Keywords: MF918; Insects; Crops; MF